2023
DOI: 10.1089/eco.2022.0080
|View full text |Cite
|
Sign up to set email alerts
|

Nature Experiences in Childhood as a Driver of Connectedness with Nature and Action for Nature: A Review

Abstract: As many studies show, action for nature is related to connectedness with nature, and both have roots in nature experiences during childhood and youth. Through a literature review, we combine empirical studies on the interplay between experiences in nature during childhood and youth, connectedness with nature, and action for nature and uncover a new way of structuring understandings of connectedness with nature: humans and nature as separate yet related entities (intertwined), one as part of the other (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Research on connectedness with nature has increased considerably over the past few decades [13,21,22], and several concepts and measures have been developed, with strong convergence among them, but also differences that need to be recognized [23]. Connectedness with nature has proved to be a useful concept in multiple disciplines; thus, it risks becoming a catch-all term, making it challenging to have a comprehensive understanding of the concept [16].…”
Section: Meanings Of Connectedness With Naturementioning
confidence: 99%
See 3 more Smart Citations
“…Research on connectedness with nature has increased considerably over the past few decades [13,21,22], and several concepts and measures have been developed, with strong convergence among them, but also differences that need to be recognized [23]. Connectedness with nature has proved to be a useful concept in multiple disciplines; thus, it risks becoming a catch-all term, making it challenging to have a comprehensive understanding of the concept [16].…”
Section: Meanings Of Connectedness With Naturementioning
confidence: 99%
“…Connectedness with nature has proved to be a useful concept in multiple disciplines; thus, it risks becoming a catch-all term, making it challenging to have a comprehensive understanding of the concept [16]. Recent review articles have structured this diversity in terms of, for example, different dimensions of connectedness [13] and types of connectedness [22]. Previous studies showed that the meaning ascribed to connectedness with nature requires considering a specific context, as it may differ depending on the type of nature [29,30] or the cultural context considered [28].…”
Section: Meanings Of Connectedness With Naturementioning
confidence: 99%
See 2 more Smart Citations
“…Emerging in the 1980s, SLE research seeks to understand what early life experiences motivate people to enter environmental protection pathways ( Tanner, 1980 ; Payne, 1999 ; Chawla, 2020 ; Chawla and Gould, 2020 ; Van Heel et al, 2023 ) or to understand the antecedents behind broader environmental protective value and behaviors ( Howell and Allen, 2017 ; Rosa et al, 2018 ). Within SLE research, engaged persons have named nature experiences as formative ( Williams and Chawla, 2016 ; Howell and Allen, 2017 ; Barratt Hacking et al, 2020 ), which may include, for example, camping and hiking outdoors.…”
Section: Conceptual Frameworkmentioning
confidence: 99%